The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/biom9110685
|View full text |Cite
|
Sign up to set email alerts
|

An Insight into Storage Lipid Synthesis by Yarrowia lipolytica Yeast Relating to Lipid and Sugar Substrates Metabolism

Abstract: Single cell oil (SCO) is the lipid accumulated in the cells of oleaginous microorganisms. Cellular lipids can be synthesized in two different pathways: de novo by metabolizing hydrophilic substrates and ex novo by fermenting hydrophobic substrates. The aim of the study was to evaluate the effect of carbon source (glucose and olive oil) in the culture medium on the course of microbial oil accumulation in Y. lipolytica cells. The level of selected gene expression by real time quantitative PCR method was investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 25 publications
1
22
1
Order By: Relevance
“…De novo accumulation of cellular lipids involves citric and isocitric acids accumulation as the tricarboxylic acids cycle is blocked. Meanwhile, Fabiszewska et al [ 21 ] indicated that de novo lipid biosynthesis could occur despite the presence of fatty acids in the medium, and the synthesis of storage lipids in the presence of lipid carbon sources could be carried out with the use of both pathways in Y. lipolytica cells (de novo and ex novo). In the present study, the low pH of supernatant and the composition of microbial oil might have acknowledged the hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…De novo accumulation of cellular lipids involves citric and isocitric acids accumulation as the tricarboxylic acids cycle is blocked. Meanwhile, Fabiszewska et al [ 21 ] indicated that de novo lipid biosynthesis could occur despite the presence of fatty acids in the medium, and the synthesis of storage lipids in the presence of lipid carbon sources could be carried out with the use of both pathways in Y. lipolytica cells (de novo and ex novo). In the present study, the low pH of supernatant and the composition of microbial oil might have acknowledged the hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…γ-decalactone [19], carotenoidse.g. β-carotene [20], organic acids-α-ketoglutaric, succinic, citric and pyruvic acids [21], lipases-enzymes used in food production, for water purification or as an ingredient in detergents [22], SCP (Single Cell Protein)-proteins of microbiological origin that can be used as feed additives [23], SCO (Single Cell Oil)-microbiological oil which is a source of essential unsaturated fatty acids (EFA) with valuable properties for both humans and farm animals [5,24].…”
Section: Yarrowia Lipolytica-a Non-conventional Yeast Species That Degrades Hydrophobic Substratesmentioning
confidence: 99%
“…In the studies described in this paper, lipid substrates were used in medium, so the ex novo pathway, which is independent of nitrogen limitation, was expected to take part in microbial oil synthesis. Meanwhile, the use of a high ratio of carbon to nitrogen source content in the culture medium turned out to be equally beneficial and reasonable as it was claimed for de novo route, what was also hypothesized by Fabiszewska et al (2019). Source/ ród o: own study based/opracowanie w asne.…”
Section: Resultsmentioning
confidence: 78%